Competitiveness of Indonesian Rice Prices in The International Market - Hutapea Ronald T.P.; Prayogo Ramadhan Rizky; Meity Aneke Tulalo; Ngongo Yohanis (E3S Web of Conferences, 2022)
More than 40 countries produce world rice, only six major exporting countries, namely India, Vietnam, Thailand, Pakistan, Myanmar, and the United States. The availability of rice on the world market annually ranges from 39-42 million tons that 40% of it imported by Asian countries, and China imports 6 million tons per year. Retail rice prices in Japan are USD 5.20/kg, Saudi Arabia USD 2.30/kg, and in Africa around USD 1.0 / kg, higher than Indonesia. The price of medium rice offered in the world market ranges from USD 0.34 - USD 0.4 per kg, while the price of special rice is USD 1,000/ton or more. Indonesia has the opportunity to export Basmati and aromatic rice to Japan and Saudi Arabia, which purchased at high prices. This export opportunities driven by reciprocal bilateral trade. Rice export to African countries needs to be explore under bilateral trade agreements. Indonesia has chance to export rice if it is able to consistently achieve a production surplus of at least 2 million tons per year. At the stage of exports, the role of the government needed in the form of tax breaks, quality assurance certification and subsidies for the rice production process.